Lateral diffusion of phospholipids in the plasma membrane of soybean protoplasts: Evidence for membrane lipid domains - Metcalf, Thomas N. (1986)
Fluorescent lipid and phospholipid probes were incorporated at 4°C into soybean protoplasts prepared from cultured soybean (SB-1) cells. Fluorescence microscopy showed that the plasma membrane as well as the nucleus were labeled. Fluorescence redistribution after photobleaching (FRAP) analysis was performed on these cells at 18°C to monitor the lateral mobility of the incorporated probes. After labeling at low concentrations (40 μg/ml) of phosphatidyl-N-(4-nitrobenzo-2-oxa-1,3-diazolyl)ethanolamine (NBD-PtdEtn), a single mobile component was observed with a diffusion coefficient (D) of ≈3 × 10(-9) cm(2)/sec. After labeling at higher probe concentrations (≥100 μg/ml), two diffusing species were observed, with diffusion coefficients of ≈3 × 10(-9) cm(2)/sec (“fast”) and ≈5 × 10(-10) cm(2)/sec (“slow”). Similar results were observed with fluorescent derivatives of phosphatidylcholine and fatty acids. In contrast to these results, parallel analysis of 3T3 fibroblasts, using the same probes and conditions, yielded only a single diffusion component. These results suggest that the soybean plasma membrane may contain two distinct lipid domains in terms of lipid mobility. Consistent with this idea, experiments with soybean protoplasts yielded a single diffusion component under the following conditions: (i) labeling with NBD-PtdEtn (100 μg/ml), FRAP analysis at 37°C (D = 1.1 × 10(-8) cm(2)/sec); (ii) labeling with NBD-PtdEtn (100 μg/ml), FRAP analysis at 18°C in the presence of 2 mM EGTA (D = 4.2 × 10(-9) cm(2)/sec); (iii) labeling with 5-(N-dodecanoyl)aminofluorescein (a short-chain lipid probe), FRAP analysis at 18°C or 37°C (D = 2.5 × 10(-8) cm(2)/sec). These results suggest that the plasma membrane of soybean cells may contain stable immiscible domains of fluid and gel-like lipids.